2008
DOI: 10.1007/s11096-008-9230-7
|View full text |Cite
|
Sign up to set email alerts
|

Post-discharge medication reviews for patients with heart failure: a pilot study

Abstract: This study provides evidence for the feasibility of a post-discharge pharmacy service for patients with heart failure although barriers to implementation have been identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 20 publications
0
39
0
Order By: Relevance
“…65,79 Key processes A range of CMR models were evaluated. This included CMRs which involved pharmacist 22,44,53 Findings of qualitative work also supported these referral pathways, with stakeholders highlighting the use of pharmacists, nursing staff and other health providers as sources for CMR referrals. 63,64 Studies also reported CMRs undertaken by an accredited pharmacist working in a medical practice, 10,33,42,45 or as part of an ACAT (n ¼ 2), 23,51 community mental health team (n ¼ 1), 35,63 or palliative care team (n ¼ 1).…”
Section: Participant Characteristicsmentioning
confidence: 96%
See 2 more Smart Citations
“…65,79 Key processes A range of CMR models were evaluated. This included CMRs which involved pharmacist 22,44,53 Findings of qualitative work also supported these referral pathways, with stakeholders highlighting the use of pharmacists, nursing staff and other health providers as sources for CMR referrals. 63,64 Studies also reported CMRs undertaken by an accredited pharmacist working in a medical practice, 10,33,42,45 or as part of an ACAT (n ¼ 2), 23,51 community mental health team (n ¼ 1), 35,63 or palliative care team (n ¼ 1).…”
Section: Participant Characteristicsmentioning
confidence: 96%
“…10,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][36][37][38][39][40][41][42][43][44][46][47][48][49][50][52][53][54][55][56][57][58][59][60][61] Some studies investigated CMR in particular demographic groups including older people (R65 years, n ¼ 10) 24,31,[45][46][47][48]51,[55][56][57] and war veterans, widows and dependents (n ¼ 5). 52,[55]…”
Section: Participant Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because heart failure medications are titrated rapidly during hospitalization, accurate prescriptions that pay attention to dosing, electrolyte management, and monitoring of renal function are important shortly after discharge. 69 It is well accepted that the institution of optimal heart failure pharmacological therapy during hospitalization is associated with improved outpatient adherence. 70,71 …”
Section: Acute Heart Failurementioning
confidence: 99%
“…1,3,4,[7][8][9] The risk of having an adverse drug event is greatest during the first 7 to 10 days after discharge, which is a particular concern for primary care providers (PCPs) who may not be able to offer patients appointments within this time frame. 10 A pharmacy intervention immediately after discharge may address this concern.…”
Section: Introductionmentioning
confidence: 99%